Handlungsorientierter Fremdsprachenunterricht empirisch Studien zu schulischen und universitären Lehr-/Lernkontexten - Delius, Katharina; Surkamp, Carola; Wirag, Andreas (Universitätsverlag Göttingen, 2021)
In the field of foreign-language teaching and learning, action-orientation is a didactic key principle. However, at present, empirical findings on how action-orientation can be pursued as a goal or put into practice as a teaching method in schools and at universities are scarce. Likewise, only little research has been conducted on the potentials and challenges of action-orientation from an academic perspective and from the perspective of teachers and learners so far. This volume provides an empirical contribution to the academic discourse on action-oriented approaches to foreign-language teaching and learning. While the volume's introduction gives an overview of the theoretical basis and empirical findings on action-orientation to date, the different contributions present individual studies in three areas: action-orientation in the teaching of foreign-language literature, action-oriented learning in global simulations and in school laboratories, and action-orientation in drama-/theatre-based foreign-language education.